Penguatan Karakter Sebagai Upaya Penanggulangan Kenakalan Remaja (Juvenile Delinquency) - I Ketut Tjukup; I Putu Rasmadi Arsha Putra; Dewa Gede Pradnya Yustiawan; Jimmy Z. Usfunan (Fakultas Hukum, Universitas Warmadewa, 2020)
Juvenile delinquency is an act or behavior of adolescents that is contrary to the law, religion, and norms of society, which harms others, public peace and himself. This study aims to examine juridically about juvenile delinquency as a crime, and how appropriate countermeasures can be done. This study uses normative juridical method by using interview techniques in collecting data. The results showed that juvenile delinquency is something that disturbs the security of the community in which they live, because juvenile delinquency is a crime that is an act that violates legal norms, decency and even religious norms. In addition, juvenile delinquency is a deviant act that is contrary to the applicable laws and regulations and can damage the future of adolescents, it is necessary to overcome them. Belimbing Village Government, Pupuan Subdistrict, Tabanan Regency has made a breakthrough in tackling juvenile delinquency crime by making preventive countermeasures with a religious-communal approach.